Navigating relational turbulence in the wake of weight loss transitions: A support marshaling analysis. Issue 3 (8th September 2020) - Crowley, John P.; Burke, Tricia; Denes, Amanda; Allred, Ryan; Carberry, Emmalene
Abstract: The current study sought to investigate how individuals optimize their partner's support during a weight transition to accomplish their weight loss goals. A theoretical model was tested to determine the role of support marshaling in managing the relational turbulence associated with weight transitions. Path modeling broadly identified that support marshaling is a useful framework from which to consider how relational turbulence associated with weight transitions influences health behaviors. The results identify that partner facilitation and interference are both directly related to health behaviors and indirectly related to health behaviors through support marshaling. Theoretical implications for relational turbulence and support marshaling are discussed with regard to their ability to account for weight‐related behavior changes.